Analisis User Experience Website Sibela Proses Stock Opname di PT Bank Mandiri dengan Metode User Experience Questionnaire Cabang Plaza Mandiri dan Sudirman Jakarta - Zaenudin, Muhamad Ridwan; Syahputra, Ade; Bintoro, Ketut Bayu Yogha (Institut Teknologi Adhi Tama Surabaya, 2025)
The problem of card discrepancies during stocktaking is complicated for companies. The use of website inventory helps minimize the difference. The stock-taking process is also important in managing card stock at PT Bank Mandiri. However, some employees are reluctant to help with card data collection during sales. Users feel burdened by additional work and complicated applications, so they need to learn first to help with inventory. Therefore, user experience is an important factor. This study analyzes how users perceive and interact with the 'Sibela' website in overcoming card discrepancies during stock-taking. Data was collected through questionnaires using the Slovin method. The conclusion of the study shows that the clarity and novelty aspects of the SIBELA website scored lower than other aspects. Users had difficulty understanding the layout, navigation or information presented and felt the design or features were less relevant. Improvements need to focus on increasing the clarity of the interface, presenting information in a more structured manner, intuitive navigation, and updating designs and features to make them more modern and in line with technological trends. This step is expected to improve the user experience, so that the SIBELA website is more effective in supporting stock-taking.